ANALYSIS OF STUDENTS’ INCORRECT ANSWERS IN A MATHEMATICAL TEST: AN INSIGHT ON STUDENTS’ LEARNING BASED ON SOLO TAXONOMY AND ERROR ANALYSIS - Kusmaryono, Imam (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2018)
Students' incorrect answers in a mathematics test provide insight into their mathematical ability and can be used as a foundation to formulate effective countermeasures. Thirty students' answers in a mathematical test were analyzed, and students with the highest rate of incorrect answers were interviewed individually to delve further on circumstances that contributed to their results. Results suggested that 45.8% of students made varying degrees of mistakes in answering the questions, with five students performing the poorest. Inadequate understanding of mathematics concepts and students' disposition contributes to students' incorrect answers.